Pathology of Incidental Pseudomonas Aeruginosa Infection in a Piglet - Garima Chahar; Sidhartha Deshmukh; Tania Gupta; Harmanjit Singh Banga (The Indian Veterinary Journal, 2023)
A case of Pseudomonas aeruginosa was diagnosed in a piglet. Detailed pathological and microbiological reports are presented and discussed in detail.